On the Role of Metals in Nitrogen-Doped Carbon Electrocatalysts for Oxygen Reduction - Masa, Justus; Xia, Wei; Muhler, Martin; Schuhmann, Wolfgang (Angewandte Chemie International Edition, 2015)
The notion of metal-free catalysts is used to refer to carbon materials modified with nonmetallic elements. However, some claimed metal-free catalysts are prepared using metal-containing precursors. It is highly contested that metal residues in nitrogen-doped carbon (NC) catalysts play a crucial role in the oxygen reduction reaction (ORR). In an attempt to reconcile divergent views, a definition for truly metal-free catalysts is proposed and the differences between NC and M-Nx/C catalysts are discussed. Metal impurities at levels usually undetectable by techniques such as XPS, XRD, and EDX significantly promote the ORR. Poisoning tests to mask the metal ions reveal the involvement of metal residues as active sites or as modifiers of the electronic structure of the active sites in NC. The unique merits of both M-Nx/C and NC catalysts are discussed to inspire the development of more advanced nonprecious-metal catalysts for the ORR.
Keywords: carbon · doping · electrocatalysis · metal-free catalysts · oxygen reduction